Study on Maximum Scour Depth at River Reach of Shantou Bay Subsea Tunnel Project - YANG Chen; GAO Shengjie; CHEN Guanming; ZHANG Shuohan (Renmin Zhujiang)
This paper studies the flow pattern and riverbed scouring at the river reach of Shantou Bay Subsea Tunnel Project through the river model test and analyzes the maximum scour depth of the riverbed near the project under unfavorable hydrological conditions.The results show that the maximum flood velocity at the tunnel section is above 1.5 m/s under unfavorable hydrological conditions,and riverbed scouring is obvious in the main channels of the left and right branches.The maximum scour depth of the riverbed at the tunnel site is 6.40 m and 5.24 m under the once-in-three-century and once-in-a-century hydrological conditions,respectively.The envelope results of the maximum scour depth at the tunnel section can provide a basis for determining the reasonable buried depth of the project,and the research results can provide reference for similar projects in Shantou Bay.